2004
DOI: 10.1902/jop.2004.75.9.1269
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Effect of Ultrasonic Scalers on Titanium Surfaces: An In Vitro Study

Abstract: In this preliminary study, the new ultrasonic scaler and conventional ultrasonic scaler were shown to be useful for removing artificial debris and produced no significant damage to titanium surfaces compared to plastic scalers. We concluded that new and conventional ultrasonic scalers with a non-metal tip would be suitable for implant maintenance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 10 publications
2
55
2
Order By: Relevance
“…Ultrasonic or piezoelectric scalers with plastic or carbon tips have also been shown to be effective without damaging implant surfaces. [9][10][11] The nonporous titanium surface calculus that forms around implants tends to be softer than calculus adhering to a natural tooth and is mostly supra-gingival. Occasionally, harder deposit around an implant may be found, which can be removed using a product like SofScale (Dentsply Professional, York, PA, USA) before scaling to further reduce the risk of scratching the implant during calculus removal.…”
Section: Review Article Baseline Radiographs-mentioning
confidence: 99%
“…Ultrasonic or piezoelectric scalers with plastic or carbon tips have also been shown to be effective without damaging implant surfaces. [9][10][11] The nonporous titanium surface calculus that forms around implants tends to be softer than calculus adhering to a natural tooth and is mostly supra-gingival. Occasionally, harder deposit around an implant may be found, which can be removed using a product like SofScale (Dentsply Professional, York, PA, USA) before scaling to further reduce the risk of scratching the implant during calculus removal.…”
Section: Review Article Baseline Radiographs-mentioning
confidence: 99%
“…These tips are usually made of carbon fiber, titanium, Teflon®, graphite, or plastic. A number of studies have demonstrated that ultrasonic tips designed for implant maintenance do not cause significant damage at the macroscopic level [50][51][52]. Paradoxically, some investigators have proposed the use of instruments that deliberately flatten the microscopically rough implant surface to reduce its roughness and thereby area available for the attachment of bacteria [53,54].…”
Section: Cavitation-based Approachesmentioning
confidence: 99%
“…A number of studies have demonstrated that ultrasonic tips designed for implant maintenance do not cause significant damage at the macroscopic level. 48,60,61 Paradoxically, some investigators have proposed the use of instruments that deliberately flatten the microscopically rough implant surface to reduce its roughness and thereby area available for the attachment of bacteria. 62,63 This appears to be a compromise since the original goal has always been to remove biofilm without causing any surface modifications.…”
Section: Cavitation-based Approachesmentioning
confidence: 99%
“…Nevertheless, these suffer from the same limitation as hand instruments in that they cannot access the undercut regions of threads. 48 A number of manufacturers have released so-called 'implant safe' ultrasonic inserts, 61 which are made of carbon fibre, silicon or plastic. There is some evidence that ultrasonic scaler tips designed for implant debridement do not modify the surface topography excessively.…”
Section: Ultrasonic Scalersmentioning
confidence: 99%
See 1 more Smart Citation